Residents’ Democratic engagement in public housing and urban areas – structures, formalities and technologies - Bertelsen, Olav W.; Korsgaard, Henrik; Kuhn, Ingrid; Schröder Carolin; Sundblad, Yngve; Tollmar, Konrad (Aarhus Series on Human Centered Computing, 2015)
The workshop gathers people from various sectors inside and outside academia to discuss the current state of, and the prospects for IT in the support of residents’ democratic engagement in, and around, public housing.